ANALYSIS OF 21ST CENTURY SKILLS THROUGH THEMATIC LEARNING IN ELEMENTARY SCHOOLS - Fitri Siti Sundari, Lina Novita, Eka Herlina (Universitas Pakuan, 2023)
1st century skills are skills related to critical thinking skills and are learning behaviors related to problem solving. The development of the 21st century is characterized by the sophistication of the field of technology, this sophistication has an impact on a variety of information that can be accessed quickly by anyone and anywhere. Skills in the 21st century are needed so as not to be left behind by developments in science and technology. Therefore teachers must have creativity and innovation in managing learning, so that students can develop their abilities in facing the 21st century. This study aims to analyze 21st century skills in learning. Qualitative description method is used to present the findings. Data collection techniques used observation sheets, interviews, and documentation studies on learning tools, especially lesson plans. Data processing was carried out using triangulation techniques, where data were analyzed, reduced, and described. The results of the analysis of the observation of the learning process found that teachers have carried out learning that leads to higher-order thinking skills and 21st century skills. Even so, teachers are still unable to apply all 4C skills in learning activities. This happens because teachers do not fully understand 21st century skills and assume that these skills are the same as higher order thinking. Therefore efforts are needed to develop teacher abilities through training or workshops on 21st Century skill.